Inclusion and distortion properties for certain meromorphically multivalent functions. Issue 7 (17th November 2017) - Liu, Jin-Lin; Srivastava, Rekha
Abstract: Two new subclasses Hp, k ( λ, A, B ) and Qp, k ( λ, A, B ) of meromorphically multivalent functions starlike with respect to k -symmetric points are introduced. Distortion bounds and inclusion relations for these subclasses are obtained.